Gascoyne Growers Market: A sustainable health promotion activity developed in partnership with the community - Payet, J.; Gilles, M.; Howat, Peter (Blackwell Publishing, 2005)
Objective: To explore the social, health and economic impact of a farmers’ market on a small rural community in the north of Western Australia. Design: Qualitative and quantitative research using a random structured intercept survey, and focus group interviews around four domains of social capital: economic impact, governance and capacity building, healthy public places and social and civic participation. Setting: The Gascoyne Growers Markets in Carnarvon. Subjects: One hundred consumers and 28 market stallholders. Results: Consumers demonstrated community pride and an increase in fruit and vegetable consumption since they commenced shopping at the markets. The stallholders appear to have gained economically, professionally and socially from the market experience. Conclusions: The Gascoyne Growers Markets demonstrate a sustainable health promotion activity developed in partnership with the community. It has contributed to the local economy, providing local quality fruit and vegetables directly to the community while also increasing social capital and creating a healthy public space.